Destiny of Destinations: Can TDM Help? - Zsuzsanna Bacsi; Ernő Kovács; Zsuzsanna Lőke; Krisztián Horváth (DETUROPE)
Tourism destination management (TDM) is a popular catchword of current tourism research. A research, co-financed by the European Union through the Hungary-Croatia IPA Cross-border Co-operation Programme, within the project ’Health &Rural Tourism DM Model’ (project no.: HUHR/1101/2.1.3/0006), was carried out in 2013 to analyse the specialities of TDM in health tourism destinations, the physical and human resources of such destinations, aspects of sustainability and competitiveness, the main factors of success. Primary data were collected by surveys and interviews carried out in six spa towns of Western Hungary. The main findings indicated, that the major natural natural endowment is medicinal water in the research area, tourism infrastructure and superstructure are sufficient, although the range of services, and marketing of health tourism services should be improved. Destination management organisations perform least efficiently in attracting investors. The attitudes of stakeholders of the tourism sector towards the idea of TDM differ, while in less successful destinations they are more inclined to cooperate this way, they are rather reluctant to do so in successful destinations. Assessing the traits of tourism service providers, the natural assets, the local community and the targeted tourist segments a general model of health tourism destinations is outlined by the four componenets of the well-known VICE model.